Spontaneous Thrombosis in Giant Aneurysm of the Anterior Communicating Artery Complex in Pediatric Age: Five-Year Follow-Up - Vítor M. Gonçalves; N. Cristino; M. Cunha e Sá (Case Reports in Vascular Medicine)
Intracranial aneurysms are rare in the pediatric population, especially in infancy, representing less than 1% of all aneurysms. In this age group, they are more frequent at the carotid bifurcation and in the posterior circulation, with a greater number of giant aneurysms and spontaneous aneurysm thrombosis when compared with the adults. They are life-threatening, and, therefore, early investigation, characterization of the lesion, and treatment are essential. The appropriate management depends on the child’s condition, aneurysm characteristics, and the experience of a multidisciplinary team. Noninvasive and radiation-free imagiological studies play an important role in the diagnosis and follow-up of these young patients. We present the case of a 3-month-old boy with an intracranial hemorrhage secondary to the rupture of a giant aneurysm of the anterior communicating artery complex, with spontaneous thrombosis, which is a rare situation due to its location. A conservative approach was assumed and noninvasive evolutive imagiological studies revealed a reduction in the thrombosed aneurysm size and no signs of recanalization. The child recovered to his baseline neurological condition and has had no rehemorrhage until 5 years of follow-up.